Association between social exclusion and loneliness among older adults in Europe - Mercan, Murat Anil; Cebeci, Ali Fehim (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
ObjectivesThis study explores how five domains of social exclusion relate to loneliness among older adults across four geopolitical regions in Europe.MethodEmploying European Social Survey (ESS) rounds 5, 6, 7, and 11, the final dataset includes 37,127 individuals aged 60+ from 29 European countries which are categorized into four geopolitical regions. Empirical estimation is based on logistic regression.ResultsLevel of income concern, infrequent social contact, and lower neighborhood safety significantly positively associated with loneliness in all five instances; the full sample and the four geopolitical regions. The relationship between level of income concern and loneliness is strongest in Western Europe, whereas associations with infrequent social contact and lower neighborhood safety are most pronounced in Southern Europe. Exclusion from basic services is a weaker but significant predictor, particularly in Central and Eastern Europe. However, civic exclusion does not show a significant relationship with loneliness among older adults.ConclusionThe findings highlight substantial regional disparities in how social exclusion relates to loneliness, potentially reflecting differences in economic conditions, welfare systems, and cultural expectations. Efforts to address financial insecurity, improve neighborhood safety, and promote social engagement may help reduce loneliness among older adults.
Keywords: Loneliness; social exclusion; social isolation; geopolitical regions; European social survey; logistic regression; RISK-FACTORS; EMOTIONAL LONELINESS; LATER-LIFE; PEOPLE; EASTERN; HEALTH; POPULATION; SUPPORT; Geriatrics & Gerontology; Psychiatry